An Unusual Intra-Vesicle Foreign Body Following Fall off a Tropical Fruit Tree. - Praveen S,; Khor TW,; James L,; Febra S,; Teh GC, (Department of Surgery, UKM Medical Centre, 2012)
Penetrating injuries to bladder occur in 20 % of cases. Synchronous bladder and rectal perforation occur in 30-64 % of cases. The management of rectal and bladder injuries depend on whether it is an extra-peritoneal or intra-peritoneal injury. We hereby, report a case of penetrating trauma in a 13 year old boy who fell off a tropical fruit (Rambutan - Nephelium lappaceum) tree. He sustained an extra-peritoneal rectal injury with intra-peritoneal bladder injury. The rectal injury was repaired primarily via per anal route while the bladder injury needed an open repair following laparotomy. Upon removal of bladder clots, a leaf of the ‘Rambutan’ tree was found intra-vesically. It was removed and bladder repaired as per standard method. We review the literature on rare intra-vesicle foreign bodies and discuss the treatment of synchronous rectal and bladder injuries.